Relationship between Intrinsic Motivation and Job Satisfaction - Ms. Sia Singh (International Journal of Indian Psychȯlogy, 2022)
Working is a quintessential part of Adulthood, most individuals aim to sustain a Job and be satisfied at work, understanding the factors which drive individuals to wake up every day and do their job to their best ability becomes imperative. The present study aims to analyze the Relationship between Intrinsic Motivation and Job Satisfaction, that is how employees are driven by internal or inherent factors to be satisfied at work. Data was collected from 130 participants, both males and females, between the ages of 25-40 years, they were asked to complete two questionnaires, the Work Extrinsic and Intrinsic Motivation Scale and Minnesota Satisfaction Questionnaire (short form). Findings of the data showed that, the two variables that is, Intrinsic Motivation and Job Satisfaction are positively significant, which translates to Intrinsic Motivation playing a part in Increasing Job Satisfaction, further it was noted that most participants were Intrinsically motivated at their job, but a majority displayed moderate Satisfaction, revealing that though Intrinsic Motivation is a factor leading to Job Satisfaction, other factors may be working along with intrinsic motivation to achieve higher Job Satisfaction.